CRITICAL DISCOURSE ANALYSIS ON TV PROGRAM OF INDONESIAN LAWYER CLUB IN PERSPECTIVE OF NORMAN FAIRCLOUGH (Execution of General Susno Duaji) - Mukhamad Muhroji (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2016)
This article reviews a critical discourse analysis implementing Norman Fairclough perspective as the basis of analysis. There are three kinds of dimensions to analyze according to Fairclough, they are sentence structure, lexicon, and meaning. This article is a report on a small CDA research by analyzing a television talk show, Indonesian Lawyer Club on TV One. The data are utterances recorded from the intercollutors in the event consisiting of nine parts of recording: Karni Ilyas, the host of the event, attorneys, Susno Duaji and his lawyer, and experts invited to the event. It was found that there were implicatures giving pragmatic force which were found in each recording which enabled watchers to understand the speaker meaning easily.